Discovery of Potent Indolyl-Hydrazones as Kinase Inhibitors for Breast Cancer: Synthesis, X-ray Single-Crystal Analysis, and In Vitro and In Vivo Anti-Cancer Activity Evaluation - Eid E. Salama; Mohamed F. Youssef; Ahmed Aboelmagd; Ahmed T. A. Boraei; Mohamed S. Nafie; Matti Haukka; Assem Barakat; Ahmed A. M. Sarhan (MDPI AG, 2023)
According to data provided by the World Health Organization (WHO), a total of 2.3 million women across the globe received a diagnosis of breast cancer in the year 2020, and among these cases, 685,000 resulted in fatalities. As the incidence of breast cancer statistics continues to rise, it is imperative to explore new avenues in the ongoing battle against this disease. Therefore, a number of new indolyl-hydrazones were synthesized by reacting the ethyl 3-formyl-1H-indole-2-carboxylate 1 with thiosemicarbazide, semicarbazide.HCl, 4-nitrophenyl hydrazine, 2,4-dinitrophenyl hydrazine, and 4-amino-5-(1H-indol-2-yl)-1,2,4-triazole-3-thione to afford the new hit compounds, which were assigned chemical structures as thiosemicarbazone 3, bis(hydrazine derivative) 5, semicarbzone 6, Schiff base 8, and the corresponding hydrazones 10 and 12 by NMR, elemental analysis, and X-ray single-crystal analysis. The MTT assay was employed to investigate the compounds' cytotoxicity against breast cancer cells (MCF-7). Cytotoxicity results disclosed potent IC50 values against MCF-7, especially compounds 5, 8, and 12, with IC50 values of 2.73 ± 0.14, 4.38 ± 0.23, and 7.03 ± 0.37 μM, respectively, compared to staurosproine (IC50 = 8.32 ± 0.43 μM). Consequently, the activities of compounds 5, 8, and 12 in relation to cell migration were investigated using the wound-healing test. The findings revealed notable wound-healing efficacy, with respective percentages of wound closure measured at 48.8%, 60.7%, and 51.8%. The impact of the hit compounds on cell proliferation was assessed by examining their apoptosis-inducing properties. Intriguingly, compound 5 exhibited a significant enhancement in cell death within MCF-7 cells, registering a notable increase of 39.26% in comparison to the untreated control group, which demonstrated only 1.27% cell death. Furthermore, the mechanism of action of compound 5 was scrutinized through testing against kinase receptors. The results revealed significant kinase inhibition, particularly against PI3K-α, PI3K-β, PI3K-δ, CDK2, AKT-1, and EGFR, showcasing promising activity, compared to standard drugs targeting these receptors. In the conclusive phase, through in vivo assay, compound 5 demonstrated a substantial reduction in tumor volume, decreasing from 106 mm³ in the untreated control to 56.4 mm³. Moreover, it significantly attenuated tumor proliferation by 46.9%. In view of these findings, the identified leads exhibit promises for potential development into future medications for the treatment of breast cancer, as they effectively hinder both cell migration and proliferation.